The control of pain - A critical discourse analysis of Socialstyrelsens guidelines for Endometriosis - Lidberg Rosenlind,Rebecka (2025)
This thesis analyzes Socialstyrelsens (Swedish Social Services) guidelines for endometriosis healthcare, with the aim of understanding the social aspects of the medicalized field of endometriosis. Former research on transnational and Swedish endometriosis experience, studies on endometriosis guidelines and Socialstyrelsens’ guidelines for healthcare, is presented to contextualize the project. The thesis’ methodological framework consists of feminist critical discourse analysis, based on the writings of Fairclough and feminist reflections on discourse, power and reflexivity. The theoretical framework draws upontheories on discourse and biopower, workfare, gender and the body, feminist bioethics as well as theories on the sociology of pain. The critical discourse analysis of the Socialstyrelsens guidelines highlights four main findings. The first is the centrality of fertility in the document while lacking discussions on the social aspects of reproduction. The second section highlights that the social perspectives in relation to pain are not accounted for. The third finding reveals how the guidelines emphasise the importance of endometriosis treatment with the overall goal of being able to lead 'normal' working life and enforces able bodied as the norm. The last theme addresses the ambivalences in the representation of gender in the document, and critically analyzes feminizing practices.
Keywords: Endometriosis; Socialstyrelsen; pain; queer theory